Portal Vein Pulsatility, A Better Indicator of Volume Status in COVID-19? - Gonzalez, Filipe; Martins, Duarte; Bacariza, Jacobo; Gomes, Rui; Fernandes, Antero (Cardiology and Cardiovascular Medicine, 2020)
Abstract not available in the source database.